Práticas informacionais no cotidiano de pessoas com restrições decorrentes de alergias e intolerâncias alimentares - Silva, Marciana Siqueira da (2021)
It deals with informational practices in the daily lives of people with restrictions resulting from food allergies and intolerances. From this perspective, it presents the informational practices of the group analyzed in the scope of Information Science, presenting the following question: How are the informational practices of people with food allergies and intolerances? The study's general objective is to show how informational practices by people with dietary restrictions take place, with a view to improving quality of life. As for the specific objectives, the following were outlined: to identify occurrences or events that contribute to the constitution of information practices; verify possible barriers that allergic and intolerant people experience in the search for information for quality of life and food safety; indicate the information search and use processes carried out by allergic and intolerant people based on the model proposed by Pamela McKenzie; and show how social networks influence and contribute to the informational practices of people with food restriction. In order to achieve the objectives, a descriptive research with a qualitative approach was carried out. The data collection instrument used was the semi-structured interview, with questions based on the two-dimensional model of informational practices by McKenzie (2003). To analyze and interpret the data, content analysis was used, as it was considered the most adequate for the purpose. Regarding the informational practices developed by the group with dietary restrictions, the following results were verified: a) the symptoms associated with stomach pain, itching and others, as well as self-medication, are linked to the preliminary diagnostic search practices; b) the barriers regarding the search for information highlighted by the respondents refer to the action of asking about ingredients at birthday parties and celebrations, high cost with tests and purchase of allergenic foods; c) the context of food for allergic and intolerant people goes beyond the nutritional meaning of food, realizing that they understand that the act of eating is an opportune moment for social ties to be established; d) regarding the information search processes, it was found that they occur from internet research strategies to face-to-face encounters with other subjects in everyday life; e) social networks are considered very important for those surveyed, as it is through platforms such as Youtube, Instagram and Facebook that the appropriation and sharing of information enables the exchange of knowledge in daily life. It is concluded that the informational practices of the analyzed group are built upon the need to maintain a safe food free of allergenic products, which focus on modes of interaction and connection for the exchange of knowledge and experiences in analog and digital informational spaces.